Clothes as a Spatial Border: Considering Privacy Boundaries in Indonesian Muslim Dwelling - Samsu Hendra Siwi (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
In Muslim society, the understanding of hijab varies, so the implications for space also vary. Socially, this is possible due to differences in the interpretation of the Qur'an and its implementation. Many Muslim societies operate spatial practices related to clothes and religion, and using clothing as a physical boundary reflects how a person responds to outsiders in their dwelling. The privacy zone in Muslim dwellings can be mapped through the clothing practices found there. This study uses case studies of privacy in six Muslim dwellings as seen through occupants' various clothing practices, from wearing no hijab to wearing hijab with niqab. The study found that the privacy boundaries in Muslim dwellings follow different rules in terms of privacy zones than those of general privacy and investigates the way Muslim women's clothing practices become an expression of spatial boundaries in everyday life. This study suggests the importance for designers of dwellings to consider the beliefs and cultures of inhabitants, including those related to privacy zones based on religious beliefs.